Higher premature atrial contraction burden after radiofrequency ablation vs. pulsed field or cryoballoon ablation in paroxysmal atrial fibrillation: a 3-year follow-up retrospective study - Jiang, Yongxing; Luo, Chenxu; Feng, Mingjun; Yu, Yibo; Du, Xianfeng; Shen, Caijie; Fu, Guohua; Wang, Binhao; Fang, Renyuan; Jin, He; Gao, Fang; Chu, Huimin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPulsed field ablation (PFA), a novel non-thermal energy source, has shown favorable 1-year data on the efficacy and safety profile in the treatment of paroxysmal atrial fibrillation (PAF). We sought to compare PFA, cryoballoon ablation (CBA), and radiofrequency ablation (RFA) in PAF treatment in a 3-year follow-up period.MethodsPatients with PAF undergoing first-time catheter ablation by PFA, CBA, and RFA were retrospectively included. The procedure endpoint was pulmonary vein isolation (PVI). Patients were followed with 24 h ambulatory ECG monitoring at 1, 3, 6, and 12 months and every 6 months thereafter. The primary efficacy endpoint was freedom from any atrial tachyarrhythmia >30 s occurring after the 3-month blanking period.ResultsA total of 280 PAF patients undergoing ablation with PFA (n = 65), CBA (n = 55), or RFA (n = 160) were enrolled. The mean age was 60.9 ± 8.7 years, with 55.7% male patients (n = 156). Acute PVI was achieved in all patients. Total procedural time was shortest with PFA [91.0 (85.0, 103.0) min, P < 0.001], whereas fluoroscopy time was shortest with RFA [9.0 (7.0, 10.0) min, P < 0.001]. The peri-procedural complication rate was 2.5%. The Kaplan–Meier estimated 3-year freedom from any atrial tachyarrhythmia >30 s was 76.9% with PFA, 72.7% with CBA, and 66.9% with RFA (log-rank P = 0.298). The principal finding of the study was the significantly lowest premature atrial contraction (PAC) burden in non-recurrent patients treated with PFA (0.04%) compared with CBA (0.05%) and RFA (0.11%) (P < 0.001).ConclusionAt the 3-year follow-up, arrhythmia freedom was similar in PFA, CBA, and RFA in patients with PAF. PFA and CBA contributed to significantly lower PAC burden compared with RFA in patients without recurrence.